Utilization of canny and velocity bunching algorithms for modelling shoreline change - Marghany, Maged; Hashim, Mazlan (2006)
This paper introduces new method for simulating shoreline change from multi-SAR data. Edge detection algorithm such as Canny algorithm is implemented to identify shoreline. Automatic detection of sequence of shoreline derived from historical multi-SAR data (ERS-1 and RADARSAT-1 SAR data) used to estimate rate of shoreline change. In addition, velocity bunching model used to model the spectral energy of ocean waves from multi-SAR data. Then, rate of shoreline is simulated by using velocity bunching model. The study shows that: the maximum rate of erosion is -3.0 m/year along the coastal water of Kuala Terengganu, Malaysia. There is significant relationship between shoreline change rate estimated using Canny algorithm and ones modeled using velocity bunching model. The significant relationship is shown by high value of R2 of 0.77.